Exploring Student Engagement in University through Lecturer Competence: A Tripod 7Cs Framework - Yundianto, Devie; Khatami, Muhammad; Mutmainah, Isna; Pastika Sandi, Anggun; Nabilah, Siti; Mutiara Sani, Febi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to empirically examine and model the influence of lecturer competence on student engagement in higher education, operationalized through the Tripod 7Cs framework, at Universitas Nahdlatul Ulama Indonesia. The 7Cs framework consists of seven instructional competencies—Care, Confer, Captivate, Clarify, Consolidate, Challenge, and Classroom Management—with student engagement conceptualized across three dimensions: Vigor, Absorption, and Dedication. Addressing the limited application of the Tripod 7Cs framework in higher education and non-Western contexts, this study investigates both the simultaneous and differential effects of the seven competencies on distinct engagement components. Participants consisted of 129 undergraduate students (N = 129), including 43 men (33.33%) and 86 women (66.67%), selected using convenience sampling. Data were collected via an online questionnaire. Lecturer competence was measured using the Tripod 7Cs Instrument, while student engagement was assessed using the Utrecht Work Engagement Scale for Students (UWES-S). Rasch measurement modeling was employed to ensure construct validity and reliability prior to hypothesis testing. Multiple regression analyses were conducted to examine the predictive effects of the 7Cs dimensions on each engagement component. In addition, a thematic analysis of open-ended responses was performed to triangulate the quantitative findings and provide contextual insight into students’ perceptions of effective teaching practices.The results revealed distinct and non-uniform relationships between lecturer competencies and engagement dimensions. The Captivate dimension emerged as a significant predictor of Vigor (β = 0.260, p = .044) and the strongest predictor of Absorption (β = 0.429, p < .001), indicating the central role of engaging instructional delivery in fostering energy and deep learning immersion. The Care dimension significantly predicted Vigor (β = 0.231, p = .040) and Dedication (β = 0.253, p = .020), highlighting the importance of relational and emotional support in sustaining students’ commitment to learning. Conversely, Clarify did not demonstrate a direct statistical effect on engagement, although qualitative findings underscored its role as a foundational instructional prerequisite. This study contributes novel empirical evidence by extending the Tripod 7Cs framework to higher education, demonstrating its applicability in an Indonesian, non-Western context, and revealing the differential predictive power of specific lecturer competencies across engagement dimensions. The findings offer actionable implications for faculty development, emphasizing that effective teaching in higher education requires not only instructional clarity, but also engaging delivery and caring lecturer–student relationships to foster meaningful and sustained student engagement.